Designing an Online Complaint Helpdesk Information System for PT. Albany Corona Lestari with A Website-Based Approach - Angga Aditya Permana; Galuh Hendrawan (Institut Bakti Nusantara, 2023)
The issue concerning damages to Indomaret stores typically involves hardware and software malfunctions and other mechanical equipment failures. When such problems arise, Indomaret staff contacts PT. Albany Corona Lestari's (ACL) Maintenance personnel. These ACL Maintenance personnel then respond by either remotely accessing the end user's computer or physically visiting the end user who reported the complaint to address and resolve the issue promptly. However, the current problem lies within the ACL Maintenance department at ACL Branch. The lack of a systematic complaint recording process is affecting the company's performance negatively. End user problems are not swiftly resolved, and there are instances where ACL Maintenance personnel forget about user complaints. The complaint handling process is currently not well-structured or controlled. To tackle these challenges, this research seeks to identify the issues present within ACL's complaint management system, which currently relies on telephone calls and emails. To address these problems effectively, the development of a complaint management application is crucial. Such an application can efficiently receive and manage complaints from multiple users simultaneously while ensuring that complaint reports are documented comprehensively. This research employs the Rapid Application Development (RAD) methodology to construct the complaint management application. The results of this study demonstrate that the RAD-based system has been successfully completed and is ready for implementation by ACL, marking a significant improvement in their complaint resolution process.